FACTORS AFFECTING THE ATTRIBUTES OF HALAL DESTINATIONS IN WEST SUMATRA TOURISM - Siregar, Alfi Syahrah; Gaffar, Vanessa; Monoarfa, Hilda; Andriana, Denny; Shahril, Aslinda (UNIVERSITAS NEGERI SURABAYA, 2025)
This study aims to identify, analyze, and explore indicators of halal destination attributes in the context of tourism in West Sumatra by integrating the concepts of halal and halal tourist destinations. Halal tourism is one of the fastest-growing sectors in the global tourism industry, driven by an increase in Muslim tourists, estimated to reach 230 million by 2026. As the country with the largest Muslim population in the world, Indonesia has great potential to become a significant halal tourism destination. West Sumatra, with its rich Minangkabau culture and strong Islamic values, is one of the leading destinations in Indonesia for halal tourism. The questionnaire was distributed to 400 respondents who had visited West Sumatra, with a return rate of 87.5%. Exploratory Factor Analysis (EFA) was conducted using SPSS version 24.0 for Windows, then continued with Confirmatory Factor Analysis (CFA) using Analysis of Moment Structures (AMoS) version 24.0 for Windows. The results showed that halal destination attributes among tourists in West Sumatra are influenced by three main factors: Muslim Friendly Tourism Quality (MFTQ), Cultural Tourism Quality (MFHS), and Muslim Friendly Tourism Standard (MFHS)). These findings are essential for destination managers to design effective strategies to attract and meet the needs of Muslim travelers, which is a growing market segment.